Konsep Pengujian Formil Undang-Undang di Mahkamah Konstitusi - Idul Rishan (The Constitutional Court of the Republic of Indonesia, 2021)
This study focuses on the concept of judicial review of the legislative process in the Constitutional Court. There are two research objectives to be obtained. First, the reasons for the need for judicial review of the legislative process in the Constitutional Court. Second, to offer the concept of judicial review of the legislative process in the Constitutional Court. This doctrinal legal research uses secondary data. The results of this research show that there were three factual reasons for the need for judicial review of the legislative process in the Constitutional Court. First, related to the reasons for the conception of the review. Second, the development of democracy. Third, the need for praxis. The results of this research refute the perception that judicial review of the legislative process does not have an obvious coordinate point under the constitution. Using the Rubenfeld approach, the constitution also accommodates the protection of the citizens’ constitutional rights in the due process of law-making.